Spatial Model of Land and Forest Fire Risk Index, Case Study in Central Kalimantan Province - Samsuri Samsuri; I Nengah Surati Jaya; Lailan Syaufina (FORESTA, 2012)
This article describes spatial models of land and forest fire risk in Central Kalimantan. The models were established base on human factor and biophysical factor approaches. The main objective of this research is to map out forest fire risk index in Central Kalimantan as well as to identify the major factor that significantly affect the forest fire risk itself. The study use CMA method to develop spatial model of land and forest fire risk. The mathematical model obtained from this study is: y = -0,00004x2 + 0,021x – 0,356 having R2 about 54 %. The significant factors that affect the forest fire risk are land allocation, land cover, land system and soil type. Model validation shows that the model can predict the risk fire index providing 66,76 % of accuracy.Key words: Central Kalimantan, forest fire risk, CMA, spatial model